Fine Needle Aspiration Cytology of Bone Marrow - Ahmed, Malik Mahmood; Haque, Anwar Ul (International Journal of Pathology, 2018)
Background: Fine needle is defined as a needle with a diameter of less than 0.21 mm (21 gauge). Fine Needle Aspiration Cytology is a time tested, reliable technique for diagnosis of lesions of various organs. However this has not been yet tested in bone marrow. Objective: Assess the feasibility of Fine Needle Aspiration Cytology in bone marrow. Patients and Methods Setting: Department of Pathology, Azad Jammu and Kashmir Medical College / Sheikh Zayed Bin Khalifa hospital Muzaffarabad Subjects: Fine Needle Aspiration Biopsy was first performed on 30 patients referred for conventional bone marrow aspiration examination to our department with their consent. Procedure was performed using 22 gauge needle and 10 cc syringe. Results: The Fine Needle Aspirate was quiet adequate in 27 cases (90%) revealing normal abnormal hematopoietic cells as well as non-hematopoietic elements. Conclusion: In many cases, Fine Needle Aspiration Cytology of bone marrow has great potential of replacing conventional thicker bone marrow aspiration needle which is much more painful and uncomfortable